Systemic Inflammation and Gastrointestinal Complications in HIV Patients: A Cross-Sectional Study on the Role of Type II Diabetes - Madalina-Ianca Suba; Bogdan Hogea; Ahmed Abu-Awwad; Daniela Gurgus; Roxana Folescu; Madalina-Otilia Timircan; Simona-Alina Abu-Awwad (Pathogens)
(1) Background: This study aimed to assess the association between inflammatory biomarkers and gastrointestinal side effects in HIV-positive patients on antiretroviral therapy (ART), with a specific focus on the impact of type II diabetes. (2) Methods: A total of 320 participants were divided into three groups: 120 HIV-positive without diabetes, 80 HIV-positive with type II diabetes, and 120 controls. Biomarkers such as CRP, IL-6, and TNF-α, along with gastrointestinal symptoms, were measured before and six months after ART. (3) Results: HIV-positive patients with type II diabetes exhibited significantly elevated levels of inflammatory markers and experienced more frequent gastrointestinal side effects, particularly nausea and diarrhea. (4) Conclusions: Type II diabetes significantly worsens inflammation and gastrointestinal side effects in HIV patients on ART, suggesting the need for tailored treatment approaches.